The Influence of Product Quality, Product Price, and Social Media Martketing on Purchase Decision of Wardah Products - Ausaie*, Muhammad Rizqi; Astuti, Tutut Dewi (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2024)
This research was conducted to determine the influence of product quality, product price, and social media marketing on purchasing decisions for Wardah products. This research uses a quantitative method with a total of 58 respondents, using a purposive sampling technique with the criteria that consumers have purchased Wardah products at least twice. This research was carried out using multiple linear regression analysis method which was processed using SPSS version 21 software. The data collection method was carried out by distributing questionnaires directly to respondents. The results of this research show that product quality, product price, and social media marketing influence purchase decision for Wardah product.